The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3109/14767058.2012.733743
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory distress syndrome after elective caesarean section in near term infants: a 5-year cohort study

Abstract: Late preterm infants born via elective CS are at high risk for RDS and NICU admission. The risk is influenced by each additional week spent in utero. As the incidence of CS is increasing within this population, new preventative strategies must be sought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…The lack of association between GDM and these latter outcomes in twin gestations may once again be attributed to the a priori higher rate of these complications in twins, 12,15,42 which are likely driven by the higher rate of prematurity in twins compared with singletons. 43,44 Indeed, we found that the rate of neonatal hypoglycemia in twins (either with or without GDM) was similar to that of singletons with GDM and considerably higher than that of singletons without GDM.…”
Section: Obstetrics Original Researchmentioning
confidence: 59%
“…The lack of association between GDM and these latter outcomes in twin gestations may once again be attributed to the a priori higher rate of these complications in twins, 12,15,42 which are likely driven by the higher rate of prematurity in twins compared with singletons. 43,44 Indeed, we found that the rate of neonatal hypoglycemia in twins (either with or without GDM) was similar to that of singletons with GDM and considerably higher than that of singletons without GDM.…”
Section: Obstetrics Original Researchmentioning
confidence: 59%
“…Neonatal respiratory morbidities were linked to scheduled CD and as the rates of CD increase the need for new preventative strategies to reduce respiratory morbidities are required. 4 Tita et al, conducted a large study including 24077 scheduled CD at term and found that that scheduled CD before 39 weeks was linked to respiratory complications, neonatal hypoglycemia, and admission to the NICU. 14 Preventive strategies were recommended to minimize CD related respiratory morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…common respiratory problems were TTN followed by RDS. 3,4 Respiratory complications are inversely correlated to gestational age at the time of delivery. As the gestational age increases, the respiratory complications decrease and vice versa.…”
mentioning
confidence: 99%
“…In 2016, 43% of all deliveries were concluded by caesarean section [7]. Despite epidural anesthesia and the improving quality of perinatal care, caesarean section continues to be associated with increased risks of both maternal and neonatal complications during delivery [8][9][10]. On the other hand, when the incidence of caesarean section rises above 20% in the population it is not matched by a corresponding decrease in maternal or neonatal morbidity.…”
Section: Discussionmentioning
confidence: 99%